Textural, Imaging And Heat Transfer Studies Of Oil Palm Fruitlets In Continuous Sterilser - Abbas, Saad Abdulamir (2008)

(untitled)
Commercial palm oil mills in Malaysia are using batch sterilisation process, which had considerable disadvantages and negative impact on palm oil mill industry. The aim of the study is to investigate some aspects of continuous steriliser, which may help in reducing the high operational cost of palm oil mills and provide a possibility of minimizing the oil lost that escape with effluent in which rendering the yield of oil and impacting environment. Sterilisation has a direct effect on textural properties of palm oil fruitlets. The level of sterilisation effect is proportional to the amount of heat applied on the process. A significant changes of certain parameter was observed and documented during this work.. Sterilisation causes softening of fruitlets texture and the degree of softening is proportional to the level of thermal treatment. Intensive work was carried out to determine textural analysis of the fruits and comparing the result with the sterilised samples that were collected from commercial mill. Different residence times were applied to investigate the changes in textural properties. Average values of fracturability, hardness and adhesiveness of abscission layer of sterilised fruitlets were measured using laboratory fabricated steriliser. Reading of these parameters are; 9 (gram force), 304 (gram force) and -8 (gram force. second), respectively. Standard values of fracturability, hardness and adhesiveness of mesocarp of sterilised fruitlets were 11.3 (force gram), 192 (force gram) and -5.7 (gram force. second), respectively. Comparing with fracturability, hardness and adhesiveness of abscission layer of fresh fruitlets of 23 (gram force), 1113 (gram force) and -15 (gram force. second), respectively. Standard values of hardness and cohesiveness of palm kernel nut of sterilized fruitlets were found to be 5293 (gram force) and 0.66 respectively. Compare with hardness and cohesiveness of palm kernel nut of fresh fruitlets of 15700 (gram force) and 0.94, respectively. It was observed from monitoring behavior of fruits texture during sterilisation that optimization process of residence time is fully complies with the objectives of sterilisation. Values of fracturability of abscission layer obtained from applying residence times of 30, 40, 45, 50 and 55 minutes were 10.7, 10.2, 9.9, 8.1 and 7.6 (gram force), respectively. Hardness values of abscission layer of 371, 265, 221 and 197 (gram force) were recorded when applying residence time of 40, 45, 50, and 55 minutes respectively. Values of adhesiveness of abscission layer of (-16.1), (-16), (-13), (-10.7) and (-8.4) (gram force. second) of residence times of 30, 40, 45, 50 and 55 minutes respectively were recorded. Hardness values of mesocarp of 302, 266, 205, and175 (gram force) were recorded with residence time of 40, 45, 50 and 55 minute respectively. Adhesiveness values of mesocarp of (-1.6), (-1.1), (-1.1), (-1.1) and (-0.97) (gram force. second) are obtained from applying residence time of 30, 40, 45, 50 and 55 minutes, respectively. Values of fracturability for the mesocarp are 11.6, 11, 10.2, 9.4 and 9 (gram force) were obtained from applying residence times of 30, 40, 45, 50 and 55 minutes respectively. Hardness and cohesiveness of fresh and sterilised palm kernel nut were investigated also. Hardness values of palm kernel nut of sterilised fruitlets are 11800, 8330, 7231, 5651, and 4516 (gram force) were obtained when applied the same residence times. Cohesiveness values of palm kernel nut of sterilised fruitlets are 0.82, 0.73, 0.71, 0.66 and 0.56 were obtained when applying same residence time also. A correlation between residence time and textural properties helps in the prediction of process optimization. The fruits normally reached the mills in different ripeness categories. Oil content and color of fruits are also not of same categories. Fruit color was observed in this study to be an excellent indicator on the oil content. Color criteria produced very good correlation on ripeness level. Intensive experiments were carried throughout in this study to establish a correlation between oil content and color of fruit. An emphasis was paid on red color band and oil content exhibits a regression value (R2) of 0.86. Color of fruits was measured in terms of digital number configuration. To verify the results obtained experimentally, a numerical and analytical simulation was developed. Models are proposed to solve heat transfer problems in sterilisation tunnel. Heat transfer model was developed under transient condition with constant fruit properties and no heat generation and the fruit was considered of spherical geometry. The model predicts temperature distribution at the center of fruit and its variation with time. Experimentally it was found that fruit needs to reside 47 minutes inside the sterilisation tunnel to reach 106 ºC which is the desired temperature to reach at the surface of palm kernel nut. Whereas residence time of 45 and 49 minutes were found to complete the required thermal treatment cycle using analytical and numerical simulation, respectively.